HISTORY, RECONSTRUCTION AND INTEGRATION OF THE "GOLDEN ROSE" CHORAL SYNAGOGUE INTO THE MODERN URBAN COMPLEX "MENORA" - Полюшкін, С.; Харченко, К.; Кобазєва, О. (SWorldJournal, 2026)
The article presents a comprehensive analysis of the history and architectural revival of the Choral Synagogue "Golden Rose" in Dnipro (Yaterynoslav), as well as its integration into the Cultural and Business Center "Menorah". The methodology of the reco